On the conditions of internal tide wave generation along the west coast of Mexico - AE Filonov; C Monzón; L Tereshschenko (Ciencias Marinas, 1996)
Baines’ (1982) model was used to calculate the energy flux of the barotropic M2 waves to internal waves. An estimation of their amplitudes in a section where the continental shelf declines was calculated. Fluxes and amplitudes of the internal waves are shown to be not only dependent on the barotropic tide intensity but also on its arrival angle to the shelf, which changes greatly. By using the vertical distribution of the Brunt-Väisälä frequency in the region of study, the trajectories of the energy flux (y) of the internal waves were calculated. By using bathymetric maps, the inclination of the shelf relief (α) was obtained. Our results show that α/y ≈ l is true for most of the sections in the continental slope, indicating optimum conditions for the generation of internal tides close to the Mexican Pacitic coast. According to the linear model of internal waves, an estimation of the parameters of the semidiurnal internal tides close to the continental slope and on the shelf was made.